2009
DOI: 10.1902/jop.2009.080447
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Therapy Reduces the Severity of Active Rheumatoid Arthritis in Patients Treated With or Without Tumor Necrosis Factor Inhibitors

Abstract: Background-Rheumatoid arthritis (RA) and periodontitis (PD) are common chronic inflammatory conditions. Recent studies have shown a beneficial effect of periodontal treatment on reducing the severity of active RA. This study was undertaken to further examine the effect of nonsurgical periodontal treatment on signs and symptoms of RA in patients treated with or without antiTumor Necrosis Factor (TNF)-α medications. The effect of anti-TNF-α therapy on periodontitis also was assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
277
5
28

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(347 citation statements)
references
References 30 publications
26
277
5
28
Order By: Relevance
“…Clinical studies show the co-morbidity between RA and PD, 11,[14][15][16]35 pathologies that share similar pathogenetic effector pathways such as the chronic inflammatory reaction associated with soft and mineralized tissue destruction. Indeed, RA can increase the incidence and severity of PD (independently or only partially dependent) of oral hygiene status or modifying factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies show the co-morbidity between RA and PD, 11,[14][15][16]35 pathologies that share similar pathogenetic effector pathways such as the chronic inflammatory reaction associated with soft and mineralized tissue destruction. Indeed, RA can increase the incidence and severity of PD (independently or only partially dependent) of oral hygiene status or modifying factors.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Indeed, numerous infectious agents, including periodontal bacteria, and antibodies against them have been implicated as contributory to the etiology of RA. 16,58,59 In addition, oral bacterial DNAs were found in synovial fluid of RA patients, suggesting that oral pathogens could have a perpetuating effect in joint disease.…”
Section: Experimental Periodontitis and Arthritis Interaction Ap Trommentioning
confidence: 99%
See 1 more Smart Citation
“…An important observation is that treatment of periodontal disease has a positive effect on disease activity of RA [39], although this observation needs further confirmation. Surprisingly, none of the studies on RA and periodontal disease considered microbiology, although bacteria play a primary role in the etiology of periodontal disease.…”
Section: Similarities Between Ra and Periodontitismentioning
confidence: 98%
“…Antibody response to P. gingivalis and DNA of P. gingivalis self have been found in synovial fluid of RA patients [48e50]. Experimental evidence is drawn from two controlled studies that have been conducted on the effect of periodontal treatment on RA [39,51]. Both studies showed that periodontal therapy had a beneficial effect on laboratory RA parameters and clinical symptoms of RA.…”
Section: The Bradford Hill Approachmentioning
confidence: 99%